Organic nutrient management technique for enhancing growth and physiological parameters in radish (Raphanus sativus L.) - A. ANBURANI, ANU. P. MANI, (Journal of Phytology, 2018)
Among the various technologies that boost the production of crop, nutrient management has got an important impact in maximizing the yield. Application of balanced fertilizers alone is not only the solution for this problem, application of residue free nutrients that protects the soil health and environment is very important. Here comes the concept of organic farming. Hence, a field experiment was conducted in the Department of Horticulture, Faculty of Agriculture, Annamalai University, Annamalai Nagar to study the effect of organic nutrients on growth and physiological parameters of radish. The experiment was conducted with eighteen treatments in three replications and laid out in FRBD design. The treatment includes various sources of organic manures viz., FYM, vermicompost, enriched manure along with and without use of consortium biofertilizer. Biostimulants viz., buttermilk solution and EMI were given as foliar spray at 15 days interval as 2 sprays. The intercultural operations and plant protection measures were carried out as per the recommendation. The results of the experiment revealed that application of farm yard manure @ 25 t ha-1 along with consortium biofertilizer @ 2 Kg ha-1 and EMI @ 1:1000 dilution ha-1 as foliar application recorded the highest growth parameters viz., shoot length, number of leaves and shoot weight. The physiological parameters viz., leaf area and chlorophyll content were recorded the highest in the same treatment T6.